FAMILY PLANNING VILLAGE PROGRAM IN RESPONSE TO THE USE OF LONG-TERM CONTRACEPTIVE METHOD - Naddratul Huda; Ni mal Baroya; Christyana Sandra; Iswari Hariastuti (Indonesian Journal of Health Administration, 2020)
Background: Contraceptive use in Indonesia was still dominated by short-term contraception. Thus, Family Planning Village is created for promoting a Long-Term Contraception Method (LTCM).Aim: This study analyzed the implementation of the Family Planning Village Program for LTCM use in Dukuhsia Rambipuji, Jember.Method: This study was descriptive with a mixed-method approach. All of LTCM users in Dukuhsia amounting to 24 participated in the quantitative study. While there were five informants who were selected purposively in the qualitative research, including a Family Planning field worker, Coordinator of Women Empowerment, Child Protection and Family Planning Office, a midwife, Advocate Assistant for Village Family Planning, and a cadre under the Advocate Assistant for Village Family Planning. Qualitative data were obtained through in-depth interviews while quantitative data through structured interviews using questioner. Data were then analyzed using the Miles and Huberman Models and statistical-descriptive analysis.Results: Most aspects of the input factor were not in accordance with the technical guidelines of Family Planning Village. Whereas the implementation method complies with the guidelines. Most aspects of the process factor were relevant to the guidelines, but there were still many obstacles in the implementation. Good participation in the family planning village program is only 37.5%. Since the program launch, the prevalence of long-term contraceptive use increase from 6.07% to 6.21%. However, it does not significantly increase the use of LTCM because the prevalence was much smaller than the prevalence of LTCM at the village level.Conclusion: The implementation of the Family Planning Village in Dukuhsia could increase LTCM users. However, it could not increase the ideal proportion of LTCM users. Therefore, it is necessary to improve input and process of the Family Planning Village through the Contraceptive Technology Update (CTU) training for midwives and conduct a training of LTCM use for cadres to enhance their communicative skill in campaigning the use of LCTM.Keywords: users, contraception, family planning village, implementation.